PROGNOSIS OF VISUALIZATION USAGE IN THE SCIENCE EDUCATION PROCESS - Bilbokaite, Renata (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Future education depends on many external exogenous factors - society evolution, technologic progress, teachers’ opinion and their ability to organize the education process. Science education is difficult for many students but the progress of the society definitely correlated with achievements of science. This highlights the importance of teaching biology, chemistry, physics, geography and mathematics at school. Visualization helps students to learn science education but at the moment teachers are not likely to use computer based visualization. It is important to find out the predictions of the future – whether pedagogues are planning to use various kinds of visualization. The research results show more than half of teachers believe that physical visualisation in the next five years will be used similarly to now. The same situation was identified asking teachers about paper based visualization. On the contrary, application of the computer-based visualisation in near future is foreseen as the progressive phenomenon: internet sites, interactive boards will mostly increase in the next five years; also, knowledge of students will be more often inspected by aids of computer-based tests. It is planned that 3 D visual objects, experiments, schemes and modelling will be less used.